Kepuasan pelanggan sebagai mediasi pengaruh brand image terhadap loyalitas pelanggan - Dwi Silvi Anisah; Iva Nurdiana Nurfarida (MBR (Management and Business Review), 2018)
To maintain market share, companies must be able to guarantee customer satisfaction so that customers become loyal. Companies need a brand image strategy or brand image so that it becomes the top of mind in the minds of consumers or customers. This study aims to determine the effect of brand image on customer loyalty mediated by customer satisfaction. The study was conducted at Warung Griya Bebek and Ayam Goreng Nelongso Malang. Accidental sampling technique with a total sample of 104 respondents, using a questionnaire as a research instrument. Data analysis technique used is Path Analysis. The analysis shows that brand image has a significant direct effect on customer satisfaction. Other results show that brand image also has a significant indirect effect on customer loyalty mediated by customer satisfaction